Zootopia [videorecording (DVD)] - Moore, Rich 1963-; Bush, Jared, 1974-; Howard, Byron; Goodwin, Ginnifer; Bateman, Jason; Elba, Idris; Slate, Jenny, 1982-; Torrence, Nate, 1977-; Hunt, Bonnie; Lake, Don; Chong, Thomas, 1938- (Buena Vista Home Entertainment, 2016)
Zootopia is a city like no other that is comprised of habitat neighborhoods like ritzy Sahara Square and frigid Tundratown, it's a melting pot where animals from every environment live together. But when optimistic Officer Judy Hopps arrives, she discovers that being the first bunny on a police force of big, tough animals isn't so easy. Determined to prove herself, she jumps at the opportunity to crack a case, even if it means partnering with a fast-talking, scam-artist fox, Nick Wilde.